NILAI FILOSOFIS DALAM LEKSIKON PENAMAAN MOTIF BATIK KHAS CIANJUR: KAJIAN ETNOLINGUISTIK - Wijiasih Eka Pertiwi; Syihabuddin Syihabuddin (Universitas Muhammadiyah Surakarta, 2023)
This study aims to describe the lingual form which consists of lexical and grammatical forms, the cultural meaning in the naming of typical Cianjur batik motifs accompanied by the philosophical values contained in typical Cianjur batik motifs. The research method used was the descriptive qualitative method and ethnolinguistic theory. Sources of data were obtained from literature reviews in the form of journal articles and online media sources. The main data source of the research consists of the lexicon of words and phrases for naming Cianjur batik motifs and the philosophical meanings found in Cianjur batik motifs. The data analysis method used was the intralingual and extralingual equivalent methods. The results of the study found lingual unit forms consisting of monomorphemes, affixations, phrases, and acronyms. Cultural meanings were in the form of cultural elements that describe the lexicon of typical Cianjur batik motifs. Then the philosophical values obtained were moral philosophical values, social philosophical values, cultural/customs philosophical values, and historical education. The results found in this study, namely the lexicon of typical Cianjur batik names based on lingual forms consisting of basic word forms (monomorphemic), affixed word forms (polymorphemic), phrase forms, and acronyms. In this form, there were also several categories of words and phrases that contain grammatical meanings such as categories of nouns and verbs. The cultural meaning that describes the characteristics and culture, social, history, and natural environment of the naming of the batik motifs. The naming lexicon of typical Cianjur batik motifs has a philosophical value consisting of moral values, social values, and cultural values.Keywords: lexicon, batik motifs, etnolinguistics, philosophical values